"Saved by the Bell": Near SUDEP during intracranial EEG monitoring. Issue 1 (11th January 2018) - Ba‐Armah, Duaa M.; Donner, Elizabeth J.; Ochi, Ayako; Go, Cristina; McCoy, Bláthnaid; Snead, Carter; Drake, James; Jones, Kevin C.
Summary: SUDEP is the sudden unexpected death of a person with epilepsy, when no structural or toxicological cause of death can be found. The majority of witnessed cases are reported to be preceded by a convulsive seizure and postictal hypoventilation. Here, we report an 8‐year‐old girl with drug‐resistant focal seizures secondary to a focal cortical dysplasia type IIb. While undergoing invasive intracranial monitoring with subdural and depth electrodes, she had a clinical apnea event recorded on video, followed by bradycardia, which required resuscitation. Her intracranial electroencephalogram (EEG) during the event showed diffuse slowing and attenuation of cortical activity, with bradycardia that responded to positive pressure ventilation with oxygen. This near SUDEP event was not preceded by either an electroclinical or electrographic seizure. This is the first report of a witnessed, near‐SUDEP event during intracranial monitoring. It emphasizes the fact that near‐SUDEP can occur without a preceding seizure.